2023
DOI: 10.1007/s00161-023-01190-3
|View full text |Cite
|
Sign up to set email alerts
|

The theory of scaling

Abstract: Scaled experimentation is an important approach for the investigation of complex systems but for centuries has been impeded by the want of a scaling theory that can accommodate scale effects. The present definition of a scale effect is founded on the violation of an invariance principle arising out of dimensional analysis, i.e. dimensionless equations do not change with scale. However, apart from all but the most rudimentary of systems, most dimensionless governing equations invariably do change with scale, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It was shown that first order similitude theory can accurately reproduce the full scale behaviour of large structures. An overall review on the application of this theory on different engineering domains is reported by Davey et al [21]. Till now, the applicability of finite similitude theory has been explored in the domain of linear elastic fracture mechanics and elastic-plastic fracture mechanics for the metals and alloys.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that first order similitude theory can accurately reproduce the full scale behaviour of large structures. An overall review on the application of this theory on different engineering domains is reported by Davey et al [21]. Till now, the applicability of finite similitude theory has been explored in the domain of linear elastic fracture mechanics and elastic-plastic fracture mechanics for the metals and alloys.…”
Section: Introductionmentioning
confidence: 99%